2022
DOI: 10.1007/s00421-022-04947-x
|View full text |Cite
|
Sign up to set email alerts
|

Fast and ballistic contractions involve greater neuromuscular power production in older adults during resistance exercise

Abstract: Purpose Neuromuscular power is critical for healthy ageing. Conventional older adult resistance training (RT) guidelines typically recommend lifting slowly (2-s; CONV), whereas fast/explosive contractions performed either non-ballistically (FAST-NB) or ballistically (FAST-B, attempting to throw the load) may involve greater acute power production, and could ultimately provide a greater chronic power adaptation stimulus. To compare the neuromechanics (power, force, velocity, and muscle activation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…17,36 The values generated in the current study were broadly similar to the peak power, force, and velocity values previously reported for young and older adults during isoinertial leg press contractions. 10,17,37 Our finding of greater mean (∆ 6 to 55% across loads), but not peak (∆ −2 to +7% across loads) concentric power immediately after a prior eccentric action, compared with CON-Only, in older adults is consistent with previous reports in young adults of higher mean power performance but no difference in peak power performance. 15 Mean power, as the average rate of performing mechanical work during the whole movement may provide the more meaningful metric of whole movement function, whereas peak power is based on just one instant that in this task occurs relatively late in the movement.…”
Section: Neuromechanical Differences During the Percentage Of Contrac...supporting
confidence: 91%
See 1 more Smart Citation
“…17,36 The values generated in the current study were broadly similar to the peak power, force, and velocity values previously reported for young and older adults during isoinertial leg press contractions. 10,17,37 Our finding of greater mean (∆ 6 to 55% across loads), but not peak (∆ −2 to +7% across loads) concentric power immediately after a prior eccentric action, compared with CON-Only, in older adults is consistent with previous reports in young adults of higher mean power performance but no difference in peak power performance. 15 Mean power, as the average rate of performing mechanical work during the whole movement may provide the more meaningful metric of whole movement function, whereas peak power is based on just one instant that in this task occurs relatively late in the movement.…”
Section: Neuromechanical Differences During the Percentage Of Contrac...supporting
confidence: 91%
“…It involved a comprehensive assessment of neuromechanical variables (i.e., mean, peak, and throughout the contraction measurements of force, velocity, power, and activation), over a wide range of loads typically used for resistance training and, thus, eliminated some limitations of previous studies of younger groups (e.g., less comprehensive measurements and/or a smaller range of loads) 17,36 . The values generated in the current study were broadly similar to the peak power, force, and velocity values previously reported for young and older adults during isoinertial leg press contractions 10,17,37 …”
Section: Discussionsupporting
confidence: 71%
“…Indeed, implementing strategies that promote increased muscle power and velocity during the concentric phase can be of great interest. The use of ballistic exercises, for instance, has been shown to yield greater improvements in lower limb velocity (ES: 1.1–6.0) when compared to traditional high-velocity RT at intensities ranging from 20% to 80% 1RM 10 . Thus, our results indicate that increasing the MPV by 10.0% and MP by 11.7% through HV ECC may result in clinically relevant chronic benefits, by acutely enhancing neuromuscular capacity in the elderly, at least in the upper body, with only 30% 1RM.…”
Section: Discussionmentioning
confidence: 99%
“…For comparisons regarding age groups and intensities, two-way ANOVAs (conditions*age; conditions*intensities) with repeated measures were applied for each variable, and, when appropriate, the differences were verified by Bonferroni post hoc tests. Percentage difference was calculated using the following equation: ([mean 1 -mean 2]/mean 1*100) [10]. Effect sizes (ES) were presented by Cohen's d z , as previously suggested [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation